The influence of diet of the donor animal on the initial bacterial concentration of ruminal fluid and in vitro gas production degradability parameters - Nagadi, S.; Herrero, Mario; Jessop, N.S. (2000)
Six sheep were fed twice a day on a different ratio of sheep pellets and hay (20:80 (diet 1), 40:60 (diet 2) and 80:20 (diet 3)) in a replicated Latin square design to study the effect of the host diet on the bacterial concentration of ruminal liquor and in vitro gas production degradability parameters of cellulose, glucose and hay. Bacterial DM, bacterial absorbance and the volume of gas produced in the absence of substrate increased as the ratio of sheep pellet to hay increased. The gas production degradability parameters obtained from fitting data to the model Gas = B(1 - exp-C(t-Lag)) were also affected by changing the ratio of sheep pellets to hay in the diet of donor animals. For each substrate, incubation with ruminal fluid taken from sheep fed on diet 2 or 3 gave higher (P < 0.05) asymptotic values 'B' (except for hay), rates C' of gas production and lower Lag times (cellulose and hay only) than when incubated in the ruminal fluid taken from sheep fed on diet 1. The digestibility of NDF from cellulose and hay was not affected by diet. Bacterial DM was strongly related to the absorbance of ruminal fluid and the volume of gas produced in the absence of substrate (R2 = 0.99, P < 0.001). Results suggest that changing the ratio of concentrate to hay reduces the initial bacterial concentration and affects the gas production degradability parameters but the estimation of bacterial DM either from bacterial absorbance or volume of gas produced without substrate was not affected by changing the diet of donor animal.